2018
DOI: 10.1007/s00109-018-1722-x
|View full text |Cite
|
Sign up to set email alerts
|

Valproic acid exerts specific cellular and molecular anti-inflammatory effects in post-operative conjunctiva

Abstract: Valproic acid (VPA) is a histone deacetylase inhibitor used clinically for neurological disorders. It is also potentially useful as anti-fibrotic therapy as it reduced collagen deposition in the post-operative conjunctiva. In this study, we further evaluated the effects of VPA on post-operative inflammation using the mouse model of conjunctival scarring. VPA, injected into the subconjunctiva immediately after surgery, did not cause any adverse tissue response when examined by live microscopy and produced an ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 50 publications
(60 reference statements)
0
9
0
Order By: Relevance
“…It is also possible that VPA may modulate the development of vascular abnormalities by reducing hypoxia through restraining the inflammatory response, which has a high metabolic demand for oxygen. 51 Overall, the distinct histological differences between PBS-treated and VPA-treated postoperative conjunctiva provide the evidence for the capacity of VPA to ameliorate the fibrotic phenotype, including vascular remodelling.…”
Section: Discussionmentioning
confidence: 90%
“…It is also possible that VPA may modulate the development of vascular abnormalities by reducing hypoxia through restraining the inflammatory response, which has a high metabolic demand for oxygen. 51 Overall, the distinct histological differences between PBS-treated and VPA-treated postoperative conjunctiva provide the evidence for the capacity of VPA to ameliorate the fibrotic phenotype, including vascular remodelling.…”
Section: Discussionmentioning
confidence: 90%
“…OBP-801 (OBP), a novel pluripotent epigenetic repressor of diverse genes that are involved in multiple steps of tissue inflammation and wound healing, as introduced in the present study, showed potent HDACi activity at a very low concentration, such as 1 nM, at levels that are 1/1000 times lower than the classical levels so far reported for HDACi, SAHA, valproic acid (VPA), and trichostatin A (TSA) 10,33 .…”
mentioning
confidence: 75%
“…Several reports have shown the effect of HDCAi on NF-κB activity, for instance: VPA has an inhibitory effect on NF-κB activation in human NK cells stimulated with IL-2 49 ; and TSA reduced NF-κB translocation to the nucleus in NK cells stimulated with IL-12, IL-15 and IL-18 27 . Furthermore, VPA is able to inhibit NF-κB activation in other cell populations, like monocytes 50 , macrophages 51 , dendritic cells 52 , fibroblast 53 and epithelial cells 54 .…”
Section: Discussionmentioning
confidence: 99%